TAFSIR AL-MIṢBĀH: LENTERA HATI QURAISH SHIHAB - Karman, Karman; Agnes Nuraeni Muslim; Andi Surya Abdi; Atang Suharna; Chintia Nabilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Tafsir al-Miṣbāh si one of the great labor of Indonesian tafsir mufti Quraish Shihab, which is divided into 15 volumes. This tafsir tends to use the type culture and society (adabi al-ijtimā’i), using a contextual approach. The method used in the tafsir is tahlily metodh. Hermeneutically, the method used in the tafsir al-Miṣbāh is though-tafsir pusing a socio-cultural analysis model. The nuances used in the interpretive style are social-social pusing a tekstual approach. The presence of the book of tafsir is seen as the good answer to use of tafsir books that van be understood and used by all various people, it is adapted to needs and problems society in Indonesia, which one is in education.